Development and testing of the Sleep Health And Wellness Questionnaire (SHAWQ) in adolescents and university students: composite SHAWQ scores are associated with sleep problems, depression symptoms, and academic performance - Loke, Yng Miin; Lim, Samantha; Rukmini, A. V.; Chen, Patricia; Wang, John C. K.; Gooley, Joshua J. (Frontiers in Sleep, 2023)
Sleep problems frequently arise during adolescence and early adulthood and may contribute to the onset of depression. However, few sleep health instruments have been developed for use in student populations. Here, we developed a brief sleep health questionnaire for identifying adolescents and university students with sleep problems who may be at risk of depression. In Study 1, sleep survey data in adolescents (n=1733) were analyzed by bestsubsets regression to identify the strongest predictors of self-reported depression symptoms: sleep quality, daytime sleepiness, self-rated health, frequency of staying up until 3:00 am, school day sleep latency, and gender. A 6-item Sleep Health And Wellness Questionnaire (SHAWQ) was developed using these items. Students were categorized into good, fair, and bad sleep health groups based on their composite SHAWQ scores. In Study 2, the SHAWQ was tested in adolescents (n=1777) for associations with depression symptoms and excessive daytime sleepiness. In Study 3, the SHAWQ was tested in university students (n=2040) for convergent validity with instruments for measuring sleep quality and insomnia severity, and for associations with major depressive disorder symptoms and anxiety disorder symptoms. Test-retest reliability was determined in a subset of 407 students who re-took the SHAWQ several weeks later. In Study 4, we tested whether SHAWQ scores in university freshmen (cohort 1, n=1529; cohort 2, n=1488) were prospectively associated with grade point average (GPA) over their first year. Across studies, SHAWQ scores were associated with higher depression and anxiety scores, excessive daytime sleepiness, lower sleep quality scores, and higher insomnia severity scores, demonstrating good convergent validity.Associations of SHAWQ scores with depression symptoms were stronger compared with anxiety symptoms. SHAWQ scores showed moderate test-retest reliability. Large effect sizes were observed for bad versus good sleep health for all sleep and mental health variables. In both cohorts of university freshmen, students with bad sleep health had lower academic performance based on their GPA and percentile rank. Our findings suggest that the SHAWQ could be used to screen for students in their teens and twenties with bad sleep health who would benefit from counselling for sleep and mental health.